Application of Induced Polarization and Resistivity Methods to Identify Subsurface Layers in Bauxite Deposits Area of Kendawangan, West Kalimantan - Muhardi, M; Anwar, M; Kaharudin, K (Jurnal Pendidikan Fisika Indonesia, 2022)
Kendawangan Sub-district, Ketapang Regency is one of the areas in West Kalimantan Province containing minerals of economic value, namely bauxite deposits. This study has applied both induced polarization and resistivity methods. It aims to identify subsurface layers in the Kendawangan bauxite deposit area based on resistivity and chargeability distribution. Measurements in the field apply a north-south line using the dipole-dipole configuration, have a length of 144 m, and electrode distance of 3 m. The results showed that the subsurface layer in the study area identified the presence of bauxite deposits. In addition, it showed that the subsurface layers were topsoil, bauxite deposits, saprolite, and bedrock. Topsoil has a thickness of about 1 m, and it is a product of the weathering process. The bauxite deposit has a thickness of about 9 m, and it contains the minerals aluminum oxide, quartz, hematite, and titanium oxide. Saprolite has a thickness of about 2 - 4 m, and it contains aluminum silica (kaolinite) and minerals quartz, titanium oxide, zircon, and it is a weathering product of bedrock. The bedrock is at a depth of more than 10 m, which is interpreted as volcanic tuff, sandstone, and claystone.